SAT0229 Herpes Zoster and Tofacitinib: The Risk of Concomitant Nonbiologic Therapy. (9th June 2015) - Winthrop, K.; Lindsey, S.; Fan, H.; Wang, L.; Gelone, D.; Mendelsohn, A.; Bananis, E.; Curtis, J.
Abstract : Background: Rheumatoid arthritis (RA) patients are at increased risk for herpes zoster (HZ), and treatment with tofacitinib, an oral janus kinase (JAK) inhibitor, appears to increase this risk. 1 Prior analysis from the RA development programme for tofacitinib identified Japanese and Korean patients to be at increased risk within the clinical development programme. 1 There is a need to understand whether patients using concomitant nonbiologic disease-modifying antirheumatic drugs (DMARDs; ie methotrexate [MTX]) are at higher risk than tofacitinib monotherapy patients. Objectives: To evaluate the incidence of HZ in patients receiving tofacitinib and to investigate the incidence rates (IRs) among patients using tofacitinib monotherapy and those using concomitant nonbiologic DMARDs or corticosteroids. Methods: We identified reports of serious and non-serious HZ from Phase (P)1/P2/P3 and long-term extension (LTE) studies of tofacitinib in RA patients (data cut April 2014), and calculated crude IRs for all HZ (serious and non-serious; unique patients with events per 100 patient-years [py]) with 95% CI. One of the LTE studies was ongoing at the time of the analysis (database not locked). Patients were censored at study withdrawal, development of HZ or death. In addition, within P3 studies where dose groups were balanced, we described HZ rates in stratified fashion according to concomitant nonbiologic DMARDs and baseline corticosteroid use. Results: In pooled P1/P2/P3 and LTE studies (19 studies; 6192 patients; 16 839 py of exposure) HZ was reported in 636 tofacitinib-treated patients: IR 4.0 (3.7, 4.4). IRs for tofacitinib-associated HZ varied widely across regions of enrolment, being lowest in Eastern and Western Europe (2.4 [2.0, 2.9] and 3.3 [2.4, 4.40], respectively) and highest among patients enrolled in Japan/Korea: IR 8.1 (7.0, 9.4). Within P3 studies, HZ incidence varied according to tofacitinib dose and background therapy with nonbiologic DMARDs: tofacitinib 5 mg twice daily (BID) monotherapy, 14 cases (IR 2.0 [1.2, 3.3]); tofacitinib 10 mg BID monotherapy, 22 cases (IR 2.9 [1.9, 4.5]); tofacitinib 5 mg BID with nonbiologic DMARDs, 43 cases (IR 4.4 [3.2, 5.9]); tofacitinib 10 mg BID with nonbiologic DMARDs, 50 cases (IR 5.0 [3.8, 6.6]). Crude IRs for HZ in patients enrolled outside Japan/Korea were lower, but similar trends in rates, according to background nonbiologic DMARDs and tofacitinib dose, were observed. In addition, crude HZ IRs were higher in patients using corticosteroids vs those not using corticosteroids, although total exposure time for these groups was limited (Figure 1 ). Conclusions: From univariate analysis within the P3 database of the tofacitinib RA clinical development programme, numerically higher crude IRs, with overlapping CIs, were observed for HZ in patients using higher dose of tofacitinib, combination nonbiologic DMARD therapy and corticosteroids. However, further analysis, including multivariable analysis, is necessary to thoroughly evaluate the risk of these and other factors for HZ development. References: Winthrop KL, et al. Arthritis Rheumatol 2014; 66: 2675-84. Acknowledgements: All aspects of this study were funded by Pfizer Inc. Editorial support was provided by Claire Cridland of Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: K. Winthrop Grant/research support from: Pfizer Inc, S. Lindsey Speakers bureau: Pfizer Inc, H. Fan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gelone Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Mendelsohn Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Curtis Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc